Impact of Ovarian Yield—Number of Total and Mature Oocytes Per Antral Follicular Count—On Live Birth Occurrence After IVF Treatment - Poulain, Marine; Younes, Rodine; Pirtea, Paul; Trichereau, Julie; Ziegler, Dominique de; Benammar, Achraf; Ayoubi, Jean Marc (Frontiers in Medicine, 2021)
To assess the relation between oocytes yield including total retrieved oocytes (O)c and total mature oocytes (MII) relative to the antral follicular count (AFC) (3-9 mm in diameter) and relative to anti-müllerian hormone (AMH) ng/mL level: Oc/AFC, MII/AFC, Oc/AMH and MII/AMH respectively and ART outcomes. We included retrospectively 264 IVF cycles after the first embryo transfer (ET) and after the cumulative ET (CET). The implantation rate (IR) and the live birth rate (LBR) after first ET were 31±39 % and 32.6 % respectively and after CET 35±38% and 45.1% respectively. There was a significantly higher average of Oc/AFC and MII/AFC when live birth (LB) occurred after the first ET (0.82±0.4 vs. 0.71±0.35 and 0.57±0.4 vs. 0.68±0.3 respectively, P<0.05). We reported a significantly higher average of MII/AFC when LB occurred after CET (0.66±0.3 vs. 0.56±0.30 P=0.02) in comparison to the group where no LB was obtained. Increased Oc/AFC and MII/AFC ratios were associated with the occurrence of LB and increased IR after first ET (P<0.05). Increased MII/AFC ratio was associated with the occurrence of LB and IR after CET (P=0.02 and P=0.04 respectively). After age-adjusted multivariate analyses, all these trends were confirmed (P <0.05) except for the effect of MII/AFC ratio on IR after CET. In conclusion, Oc/AMH and MII/AMH ratios have no effect on the occurrence of LBR or on IR after first ET or CET at either age grouping. Ratios Oc/ AFC and MII/AFC seem promising indicators to assess ovarian response.